Systemic Arterial Hypertension in Childhood: A Challenge Related to the Increasing Survival of Very Low Birth Weight Preterm Infants - Schoenardie, Bruna Ossanai; Guimarães, Victória Bernardes; Procianoy, Renato Soibelmann; Silveira, Rita C. (American Journal of Perinatology, 2019)
Objective To verify the prevalence of systemic arterial hypertension (SAH) and to identify possible early predictors of SAH at ages 2 and 4 years in very low birth weight (VLBW) infants.Study Design This is a prospective cohort study including inborn children with birth weight (BW) <1,500 g. Arterial blood pressure measurements were performed at 2 and 4 years. Model 1 compared children with and those without SAH at age 4. Model 2 compared children who had SAH at ages 2 and 4 with the others. SAH was diagnosed if the systolic or/and diastolic pressures were above the 95th percentile.Results A total of 198 patients were included during the 5-year study period, of whom 56% had SAH at age 4. In model 1, white matter injury (WMI) and catch-up growth at age 2 were predictors of SAH at age 4. In model 2, bronchopulmonary dysplasia, WMI, catch-up growth at age 2, and BW were predictors of SAH at 2 and 4 years. SAH at age 2 was an independent risk factor for SAH at age 4. After a multivariate analysis of model 2, BW and catch-up growth were associated with SAH.Conclusion Prevalence of SAH was high in VLBW infants; it was associated with low BW and catch-up growth at age 2.
Keywords: systemic arterial hypertension; prematurity; early childhood; neonate; child